Portraits of Displacement – Memory and Narratives of South African Durban Communities through the photographic exhibition Proclamation 73 - Cloete, Nicola Marthe; Bentel, Claudia (Taylor & Francis Group, 2022)
This paper spans two temporal locations - on the one hand it holds the historical events of indentured labour in the then British Colony of Natal in the 19th century in mind, on the other is the contemporary photographic exhibition produced in 2019, which includes images that broadly relate to apartheid era law but also extends as far back as the 1800s. We suggest there are ways in which the visually constituted archive material starts to shift our expectations and understandings of what the narratives of forced migration may mean and where their resonances may reside, particularly in the South African context. In the analysis we undertake of the exhibition and the images they encompass; we zoom in on the ongoing racialised regimes of looking and knowing and simultaneously show how these regimes have consistently been disrupted in the space of the personal family album.
Keywords: Slavery; Post-apartheid; South Africa; Memory; Representation; Race; Reconciliation; Memory making